Computational Demonstration of Isomer- and Spin-State-Dependent Charge Transport in Molecular Junctions Composed of Charge-Neutral Iron(Ii) Spin-Crossover Complexes (Vol 52 Pg 1229 2023 - Cardenas-Jiron, G; Montenegro-Pohlhammer, N (ROYAL SOC CHEMISTRY, 2024)
Correction for Computational demonstration of isomer- and spin-state-dependent charge transport in molecular junctions composed of charge-neutral iron(ii) spin-crossover complexes by Nicolas Montenegro-Pohlhammer, et al., Dalton Trans., 2023, 52, 1229-1240, https://doi.org/10.1039/D2DT02598A.